2D NiMoO4 nanowalls directly grown on Ni foam for the asymmetric electrochemical supercapacitors - Ha-Ryeon Lee; M. Shaheer Akhtar; Ahmad Umar; Ahmed A. Ibrahim; Sotirios Baskoutas; O-Bong Yang (Chemical Physics Impact, 2024)
Significant advances in the field of energy storage have enabled scientists to explore highly stable electro-active electrodes for high-performance supercapacitors. The present investigation describes the synthesis of well-ordered NiMoO4 nanowalls at 140 °C using hydrothermal synthesis, which was then grown directly on Ni foam with different reaction times. The resulting NiMoO4 nanowalls were utilized as electro-active electrodes for electrochemical supercapacitor applications. The reaction time was found to be a critical factor in achieving the ordered NiMoO4 nanowalls on the Ni foam, and at a reaction time of 12 h, the nanosheets self-organized into a nanowall-like morphology over the Ni foam. Pure NiMoO4 crystal phases with less surface imperfections were produced by the 12-hour reaction time, as demonstrated by the compositional, structural, and crystalline characteristics. As an electro-active electrode, the NiMoO4 electrode with a 12-hour reaction time showed the highest specific capacitance of 357.6 Fg−1 at 0.01 Vs−1 compared to NiMoO4 electrodes with reaction times of 6h (53.06 Fg-1 at 0.01 Vs−1) and 20h (55.4 Fg-1 at 0.01 Vs−1). The NiMoO4 electrode also demonstrated exceptional stability in an alkaline electrolyte, exhibiting less deterioration in multicycles CV after 100 repeated cycles. The excellent electrochemical properties of the NiMoO4 electrode are attributed to its unique ordered nanowall structure, which improves surface area and electrical conduction, accelerating fast redox reactions. These properties make it a promising material for use in pseudocapacitors, with implications for high-performance energy storage solutions in industrial sectors.